Exploring Burkholderia pseudomallei-specific bacteriophages: overcoming O-antigen specificity and adaptive mutation in phage tail fiber - Khrongsee, Pacharapong; Kaewrakmuk, Jedsada; Alami-Rose, Mariam; Subramaniam, Kuttichantran; Waltzek, Thomas B.; Schweizer, Herbert P.; Tuanyok, Apichai (Frontiers in Bacteriology, 2024)
Burkholderia pseudomallei, a Gram-negative bacterium inhabiting soil and fresh water, is the causative agent of melioidosis, a formidable disease in the tropics. The emergence of antibiotic resistance and the extended duration of treatment, up to 20 weeks, have posed significant challenges in combatting melioidosis. As an alternative approach, bacteriophage therapy is being explored. To identify the most promising bacteriophage for future therapeutic applications, we designed a screening process to address the barrier of phage specificity due to the O-antigen receptor diversity. By using two biosafe strains, Bp82 (O-antigen type A) and 576mn (O-antigen type B), to represent the major serotype A and B, we screened 145 phage samples collected from soil and water in southern Thailand. Ten of them demonstrated the ability to overcome differences in O-antigen types, yielding positive plaques formed on culture of both bacterial strains. Subsequently, we isolated twenty-two bacteriophages from these samples, one was adaptively mutated during the screening process, named PK23V1, which had the ability to infect up to 83.3% (115/138) of tested B. pseudomallei strains, spanning both serogroups. Employing a panel of surface polysaccharide antigen mutant strains, we explored the role of capsular polysaccharide (CPS) and O-antigens as essential components for phage infection. All isolated phages were classified into the P2-like myophage group. Additionally, our research revealed a point mutation in the phage tail fiber gene (gpH), expanding the host range of PK23V1, even in the absence of CPS and O-antigens. However, it was evident that ΦPK23V1 is a lysogenic phage, which cannot be readily applied for therapeutic use. This discovery sheds light on the receptor binding domain of P2-like bacteriophages in B. pseudomallei. Collectively, our study has identified bacteriophages with a broad host range within B. pseudomallei strains, enhancing our understanding of phage-host interactions and offering insights into the role of the phage tail fiber gene in host cell entry.